Faktor-faktor yang Mempengaruhi Keberhasilan Terapi Pasien Kusta - Sagia, Nabilla Alsa; Anggraini, Dwi Indria; Wulan, Anggraeni Janar; Sibero, Hendra Tarigan (Medula, 2024)
Leprosy is a chronic granulomatous infectious disease caused by the obligate intracellular bacterium Mycobacterium leprae (M. leprae). This disease comes from the Latin word "lepros" which means scale. M. Leprae bacteria enter the human body through 2 main routes, namely through the skin and the upper respiratory tract. Leprosy bacilli enter the human body through direct contact with the skin or nasal mucosa originating from droplets. Bacteria from droplets will survive for 2 days in a dry environment, even up to 10 days in a humid environment and low temperatures. The success of therapy for Morbus Hansen patients is expressed by RFT (Release from Treatment). RFT can be stated after the dose is fulfilled without having to undergo laboratory examination. PB (paucibacillary) patients who have received 6 doses (blister) of treatment within 6-9 months are declared RFT, without having to undergo a laboratory examination. MB (multibacillary) patients who have received 12 doses (blister) of MDT treatment within 12-18 months are declared RFT, without having to undergo a laboratory examination. The factors that play a role in the success of therapy for leprosy patients are age, gender, education, employment, knowledge, compliance with taking medication, and family support.